find the values of x such that f(x)=0, if f(x)=x^3 - 6x^2 + 11x - 6 my ans: i got f(x)=0 by substituting x=1 how to solve from there?
Follow Math Help Forum on Facebook and Google+
Originally Posted by Faz find the values of x such that f(x)=0, if f(x)=x^3 - 6x^2 + 11x - 6 my ans: i got f(x)=0 by substituting x=1 how to solve from there? We know then that $\displaystyle x-1|x^3-6x^2+11x-6$ So simplify $\displaystyle \frac{x^3-6x^2+11x-6}{x-1}=???$ to get a simple quadratic solvable by any number of ways.
i divided and got (x-1) (x-3) (x-2) ans : 1,3,2
View Tag Cloud